Service user and carer involvement in students' classroom learning in higher education. Issue 3 (3rd April 2018) - Unwin, Peter; Rooney, Joy; Cole, Charmaine
Abstract: The following article presents a small-scale qualitative study in which the student learning experiences from service user and carer (SUAC) involvement in social work, mental health nursing and social welfare courses at an English university were evaluated for any effects on student perceptions, knowledge, skills and practice. Using focus group methodology, student participants reported positive outcomes from exposure to SUAC classroom inputs such as a greater valuing of SUAC knowledge as expert knowledge, help with the development of empathy and an appreciation of constructive challenges to mainstream curricular delivery. Notes of caution were identified, particularly in respect of the sometimes unexpected levels of emotion displayed by SUAC presenters. Recommendations for meaningful SUAC involvement in higher education are made regarding the need to involve SUACs across the whole duration of a course; the need for the preparation of both students and presenters regarding boundaries; the fit of presentations with intended learning outcomes; more partnership delivery in classrooms between academics and SUACs (possibly with a differentiation between theoretical and practice inputs); the opportunities for SUACs to present their own situations as real rather than hypothetical case studies for students and the possibilities that may result from introducing a 'buddying' system between students and SUACs throughout their studies. It is suggested that the insights from this small-scale study merit further exploration on a larger scale if policy and practice in the field of service and user involvement in higher education are to move forward in an inclusive manner.